1997
DOI: 10.1002/etc.5620160615
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cation‐exchange methodology for marine toxicity identification evaluation applications

Abstract: In phase I of a standard toxicity identification evaluation (TIE) six manipulations are used to characterize toxicity. The ethylenediaminetetraacetic acid addition manipulation is most often used to indicate toxicity caused by divalent metals. An alternative approach for characterizing/identifying metal toxicity is the use of cation‐exchange chromatography. In this study, five cation‐exchange media were compared to develop a method for using cation‐exchange chromatography as part of a marine TIE. To be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Leonard, personal communication). Studies with a similar resin in metal‐deionized water mixtures demonstrated the removal of cadmium, copper, nickel, lead, and zinc from solution [37].…”
Section: Resultsmentioning
confidence: 99%
“…Leonard, personal communication). Studies with a similar resin in metal‐deionized water mixtures demonstrated the removal of cadmium, copper, nickel, lead, and zinc from solution [37].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we have investigated the use of selective sorbents added to whole sediments to reduce concentrations of ammonia in pore water. Other researchers have used selective sorbents in the development of sediment TIE procedures for nonpolar organic compounds [12] and cationic metals [13]. This approach, like the equilibrium partitioning approach used for development of sediment quality criteria [14,15], assumes that the toxicity of sediment contaminants is related to concentrations of toxicants in pore water.…”
Section: Introductionmentioning
confidence: 99%
“…A sequential treatment using the SPE column followed by addition of EDTA to column rinsate was conducted to resolve mixtures of organic and metal contaminants. A cation‐exchange column (3 ml; Supelclean™ LC‐WCX; Supelco, Bellefonte, PA, USA) [8] was used to remove metal contaminants. The cation‐exchange column was then eluted with 1 N HCl to add back bound metals to clean dilution water.…”
Section: Methodsmentioning
confidence: 99%